Community Empowerment Through Trainning Utilization About Natural Resources In The Escalation Of Natural Resources In Tumut, Boyolali - Mohamad Habibi; Sherlyna Dedha Astuti; Rizki Alfiyatun (BEMAS: Jurnal Bermasyarakat, 2022)
Tumut village is the highest hamlet located in Jrakah Village, Selo District, Boyolali Regency. Most of the livelihoods of the village Tumut community are farmers and ranchers. Besides having natural resources in the agricultural sector, also has potential in the livestock sector. Most of the hamlet communities own livestock. The livestock sector in village Tumut is not optimized due to the lack of public knowledge about how to raise livestock properly. In the dry season, farmers only rely on the rest of the grass for animal feed without providing adequate nutrition to livestock. Forage feed can be developed to be one way to meet the nutrition and protein of livestock by processing feed fermentation. Rice straw is one of the ingredients that can be used in the fermentation process to improve the quality of animal feed. Through training on feed management by means of fermentation, it can help improve the quality of livestock and be able to overcome community problems. The method used in this training is in the form of socialization and counseling and followed by direct practice regarding feed processing with the fermentation method to residents. The result of the value fermentation method is in the form of animal feed which has higher nutrition and can make it easier for farmers to find feed for livestock. Where the results of the feed produced can also last longer than ordinary grass feed.